2003
DOI: 10.1002/bem.10101
|View full text |Cite
|
Sign up to set email alerts
|

Subjective symptoms among mobile phone users—A consequence of absorption of radiofrequency fields?

Abstract: In a previous epidemiological study, where we studied the prevalence of subjective symptoms among mobile phone (MP) users, we found as an interesting side finding that the prevalence of many of the subjective symptoms increased with increasing calling time and number of calls per day. In this extrapolative study, we have selected 2402 people from the epidemiological study who used any of the four most common GSM MP. We used the information about the prevalence of symptoms, calling time per day, and number of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 5 publications
1
27
1
1
Order By: Relevance
“…The term "good" was the highest rating for respondents' health condition in the Nordic countries, Australia and Arabia, while in our study 22% of the people rated their health as very good and 59% as good. Norway [7] (N = 2828)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The term "good" was the highest rating for respondents' health condition in the Nordic countries, Australia and Arabia, while in our study 22% of the people rated their health as very good and 59% as good. Norway [7] (N = 2828)…”
Section: Discussionmentioning
confidence: 99%
“…In addition to headaches, the users of mobile phones reported fatigue and general discomfort, nausea, impaired thermoregulation [5]. Results of the questionnaire on subjective complaints of the mobile phone users conducted in Sweden, Norway, England, USA, New Zealand, Egypt, Saudi Arabia and Australia have shown that headache was the most frequently observed symptom [4,[6][7][8][9][10][11][12]. A study in Australia showed that headache, including migraine and cluster headache, appeared during or shortly after a call was ended, and often intensified during the day.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been calculated that the temperature in the head increases by not more than 0.11oC5 while using a mobile phone, although a feeling of warmth may be felt in the ear during a telephone call. 12 2) non-thermal effects: these take place with no temperature change in biological tissues. These effects have not yet been fully clarified, and are the reason for many debates among scientists.…”
Section: Biological Effects Of Radiofrequency/microwavesmentioning
confidence: 99%
“…Globalement, ces études indiquent une augmentation des symptômes subjectifs (dont des sensations de chaleur au niveau de l'oreille ou de la face, céphalées, inconfort, vertiges, difficultés de concentration, fatigue) avec l'augmentation du temps d'appel et du nombre d'appels par jour (Al-Khaiwi et Meo, 2004 ;Chia, et al, 2000 ;Hocking, 1998 ;Oftedal et al, 2000 ;Sandström et al, 2001 ;Santini et al, 2001a ;Wilen et al, 2003). Ces symptômes ont été mis en relation avec les taux d'absorption spécifique (Wilen et al, 2003) et expliqués hypothétiquement par une stimulation vestibulaire (Cox et Luxton, 2000). Des différen-ces sont parfois observées en fonction du type de téléphone mobile utilisé (900 MHz, 1800 MHz, numérique vs analogique).…”
Section: Introductionunclassified